Insights into the Foraging Behavior of Magellanic Penguins (Spheniscus magellanicus) - Gómez Laich, Agustina Marta (2018)
Between 25-30 November 2013, 2014 and 2015, miniaturized video cameras were attached to Magellanic Penguins (Spheniscus magellanicus; n = 14) in Punta Norte/San Lorenzo, Península Valdés, Chubut, Argentina. The objective was to examine prey selection, consumption of untraceable prey, and inter- and intraspecific interactions. During 56.3 hr of video footage, 1,621 dives from 14 individuals were recorded. Magellanic Penguins swam through shoals of lobster krill (Munida gregaria morph subrugosa), selectively consuming the fish, primarily anchovies (Engraulis anchoita), that were dispersed along the shoal, but did not consume the lobster krill. Magellanic Penguins captured fish on dives of less than 2 m in depth. The tagged individuals foraged with conspecifics in 2% (n = 33) of the total recorded dives. In addition, a multispecies feeding association was also documented (n = 1). Results were constrained to the upper 40 m of the water column; below this depth light level was too low for detections by video. The development of cameras with a light source and wider-angle lens are crucial to improve our understanding of Magellanic Penguin foraging behavior.